Faktor – Faktor Yang Mempengaruhi Keputusan Menginap Di Muslim Friendly Hotel Rangkayo Basa Padang - Solawati, Dila; Wulandari, Dwi Pratiwi (CV. ITTC INDONESIA, 2024)
Guest decisions in choosing a hotel are influenced by various factors. However, in the midst of increasingly fierce competition in the hospitality industry, there are still few studies that highlight the factors that influence the decision to stay at a hotel with a halal concept. This study aims to identify the most dominant factors that influence guest decisions in choosing a halal hotel, with a focus on the Rangkayo Basa Padang hotel. The research method used is quantitative method with data collection through a survey using a questionnaire to 100 guests who are currently and have stayed at Rangkayo Basa Padang hotel. The data was analyzed using Exploratory Factor Analysis (EFA) to identify the main factors that influence the decision to stay. The results of this study indicate that several dominant factors influence the decision to stay, namely image and service factors with a variant value of 58.32%; and price and halal lifestyle factors with a variant value of 7.925%. The novelty of this research is the object of research with a halal concept, as well as the results of the dominant factors that influence overnight decisions. This research provides new insights for halal hotel managers in designing more effective marketing strategies.